THE INFLUENCE OF LEARNING ENVIRONMENT ARRANGEMENT ON THE EFFECTIVENESS OF DEVELOPING COLLABORATION AND EXPRESSIVE LANGUAGE SKILLS IN EARLY CHILDHOOD - Farantika, Dessy; Prawinda, Raras Ayu; Imawati, Veni (Universitas Al-Hikmah Indonesia, 2024)
The ability to cooperate and express language is one of the developments that children must have. Providing a stimulus that is not optimal is one of the problems that triggers the problem. Class arrangement is one way that can be provided to help this development process. The aim of the research is to determine the level of effectiveness of classroom arrangements in improving cooperation and expressive language skills in early childhood. This research uses a quasi-experimental research design (quasi experiment). By using a pre-test before being given treatment and a post-test after being given treatment. This research design uses a non-equivalent pretest-pretest control group design. Data was collected through structured observation, interviews and documentation. The subjects of this research were students and teachers from group B at the Muslimat NU 14 Polowijen Kindergarten, Malang City. The results of this research show that the arrangement of the learning environment has a significant influence on the development of cooperation skills and expressive language abilities in young children. Structuring a good learning environment, including space arrangement, providing educational game tools, and creating a conducive learning atmosphere, has been proven to increase the effectiveness of children's social interactions and verbal abilities. In conclusion, the arrangement of the learning environment plays an important role in supporting the effective development of cooperation skills and expressive language abilities in young children. This research recommends that educators create learning spaces that are child-friendly and oriented towards the development of social and language skills.